Návrh zlepšení kulturního projektu - Klusáková, Ivona (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Diplomová práce je zaměřena na provedení změn ve fungování kulturního projektu pořádaného pod záštitou příspěvkové organizace. Cílem práce je provést změny, které vylepší ekonomickou situaci projektu, zvýší zájem ze strany návštěvníků a také nabízí nové možné zdroje financování. Seznamuje se základními poznatky o organizaci a samotném projektu, rolí marketingu v neziskovém sektoru. Praktickou část tvoří navrhované změny v oblasti propagace projektu, jeho financování a organizování.

The master’s thesis is focused on the changes in the functioning of the cultural project, which is organized by an allowance organization. The aim of this work is to make changes that will improve the economic situation of the project, will increase the attention and interest of visitors and also offers new possible sources of financing. The thesis begins with basic information about organization and the project as such, describes the role of marketing in the non-profit sector. The practical part consists of the proposed changes in the promotion of the project, its financing and organization.
Proposal of Development of Cultural Project
Keywords: Kultura; reklama; finance; organizování; Culture; advertisement; finance; organization